Comparison between the efficiency of two bioindicators for determining surface water quality in an urban environment - doi: 10.4025/actascibiolsci.v33i3.7725 - Oliveira-Filho, Eduardo Cyrino; Ramos, Marianni Gonçalves; Freire, Ingrid Souza; Muniz, Daphne Heloisa de Freitas (Acta Scientiarum. Biological Sciences, 2011)
This study evaluated the efficiency of two bioindicators, fecal coliforms and ecotoxicity tests, set out in CONAMA Resolution 274/00 and CONAMA Resolution 357/05, in assessment of water quality. For this study, Lake Paranoá, Federal District of Brazil, was chosen, since it is a water body directly contaminated by effluents from a sewage treatment plant. Four sampling points were chosen in accordance with the map of recreational water quality published weekly by CAESB/DF, after analysis of fecal coliforms. Samples from these points were collected for 6 months and tested on Danio rerio fish (acute toxicity) and on the microcrustacean Ceriodaphnia dubia (acute and chronic toxicity), besides measuring chemical and physico-chemical parameters. The data obtained show great consistency between the observed biological parameters, suggesting that in this urban aquatic environment, under great anthropogenic pressure, the fecal coliform bioindicator seems to be more restrictive and enough to evaluate the safety of surface water.